Türkiye’ye yönelik Türkmen göçü ve Türkiye’deki Türkmen varlığı=Turkmens’ migration towards Turkey and Turkmen population in Turkey=Hicretü't-Türkmân nahve Türkiye ve'l-vücûdu't-Türkmânî fî Türkiye. (Ankara)
38, [1] s.